N.A. Nazarbayev, second secretary of the regional committee of the Communist Party of Kazakhstan - Yedgina, G.T.; Zhumashev, R.M.; Taam, K. A.; Zuyeva, L.I. (KSU Publ., 2020)
In December 1977 at the VIII plenum of the Karaganda regional committee of the Communist Party of Kazakhstan N.A. Nazarbayev was elected second secretary of the regional committee of the Communist Party of Kazakhstan. In a new position N.A. Nazarbayev faced the same challenges as he had before, but on a much larger scale. Analysis of the report of the second secretary of the regional committee of the Communist Party of Kazakhstan N.A. Nazarbayev allowed the authors to conclude that in the period 1977–1979 N.A. Nazarbayev demonstrated all the great opportunities and hidden potential in managing people and the ability to solve vital issues, significantly strengthened the regional committee of the party, considerably expanded his sphere of influence. His energy, knowledge, experience, business qualities and great abilities began to manifest even brighter.
Н.Ә. Назарбаев — 1977–1979 жж. Қазақстан Компартиясы облыстық партия комитетінің екінші хатшысы
Н.А. Назарбаев — второй секретарь обкома Компартии Казахстана в 1977–1979 гг.
Keywords: Republic of Kazakhstan; First President; history; secretary; labor activity; Communist party; Kazakhstan; Karaganda region